2020
DOI: 10.1007/s40820-020-00516-z
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Chemodynamic Therapy by the Synergistic Effect of Co-Catalyze and Photothermal Effect Triggered by the Second Near-Infrared Light

Abstract: In spite of the tumor microenvironments responsive cancer therapy based on Fenton reaction (i.e., chemodynamic therapy, CDT) has been attracted more attentions in recent years, the limited Fenton reaction efficiency is the important obstacle to further application in clinic. Herein, we synthesized novel FeO/MoS2 nanocomposites modified by bovine serum albumin (FeO/MoS2-BSA) with boosted Fenton reaction efficiency by the synergistic effect of co-catalyze and photothermal effect of MoS2 nanosheets triggered by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…To overcome these shortcomings, the combination of nanozyme-based catalytic therapy and photothermal therapy (PTT) is a promising approach [ 24 , 25 ]. PTT is an effective method that uses photothermal reagents to generate local high temperature to treat bacterial infections under near-infrared (NIR) light irradiation [ 26 , 27 ]. Although PTT has the advantages of high controllability and minimal invasiveness, relatively high-power laser intensity can still cause side effects on healthy tissues [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these shortcomings, the combination of nanozyme-based catalytic therapy and photothermal therapy (PTT) is a promising approach [ 24 , 25 ]. PTT is an effective method that uses photothermal reagents to generate local high temperature to treat bacterial infections under near-infrared (NIR) light irradiation [ 26 , 27 ]. Although PTT has the advantages of high controllability and minimal invasiveness, relatively high-power laser intensity can still cause side effects on healthy tissues [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although PTT has the advantages of high controllability and minimal invasiveness, relatively high-power laser intensity can still cause side effects on healthy tissues [ 14 ]. Therefore, the combination of catalytic therapy and PTT can simultaneously enhance the catalytic production of ROS while reducing the collateral damage of PTT [ 15 , 27 ]. Although several nanozymes have been reported for PTT-catalytic antibacterial treatment, the treatment performance of these nanozymes is still limited [ 12 , [14] , [15] , [16] , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 @CGTC NCR could effectively ablate A549 cells in vivo and in vitro. Recently, copper ions and iron ions have been incorporated into MoS 2 to enhance the CDT effect of MoS 2 [ 371 , 372 ]. For example, Jiang et al [ 373 ] prepared MoS 2 –CuO heterostructures to promote the generation of ·OH by inducing Fenton or Fenton-like reactions.…”
Section: Multifunctional Nanoplatforms For Cancer Therapymentioning
confidence: 99%
“…Zhang et al reported a kind of BSA-modified FeO/MoS 2 nanocomposites (FeO/MoS 2 -BSA) with boosted Fenton reaction efficiency resulted from the synergistic effect of metal catalysts and the photothermal effect of MoS 2 nanosheets triggered by the second NIR light (Fig. 16 a) [ 142 ]. In the TME, the Mo 4+ on the surface of MoS 2 nanosheets not only accelerated the conversion of Fe 3+ to Fe 2+ and improved Fenton reaction efficiency but also endowed FeO/MoS 2 -BSA with good photothermal performances for photothermal-enhanced CDT and PTT.…”
Section: Combination Therapymentioning
confidence: 99%
“…16 Schematic presentation of FeO/MoS 2 -BSA for MRI and synergetic enhanced CDT/PTT ( a ). Reprinted with permission from ref [ 142 ]. Copyright 2020 Springer.…”
Section: Combination Therapymentioning
confidence: 99%